PENGGUNAAN KITAB SUCI AGAMA KRISTEN (ALKITAB) DALAM RITUAL PENGOBATAN DI MINAHASA - Ruland Supit; Theofilus Welem (P3TK, Sanata Dharma University, 2023)
The purpose of this paper is to explain the use of the holy book (Bible) in the healing rituals performed by the Tona'as in Minahasa, and aims for several groups of local belief adherents in Minahasa to carry out healing rituals that use the holy book and those who do not use the holy book and There are pros and cons in healing rituals. In the experience of the Minahasa people, the use of religious books in the process of carrying out healing rituals has had pros and cons, but this problematic situation has not made religious books disappear in the implementation of rituals. Religious books cannot be separated from sacred reality, because almost all religions have beliefs about the sacred and that belief grows through religious books as a foundation for understanding various religious realities. The theoretical approach that will be used as material for analysis is the theory of religious texts, ideology, culture and community and will also use the theory of rituals from Catherine Bell and some of the severe opinions of sociologists regarding rituals. The research method used is a qualitative method with a phenomenological approach. The results of the study show that the ritual process which includes Christian religious books, namely the Bible, is a separate way for the local community to construct their beliefs by understanding that there is a sacredization in the ritual process.